THE EFFECTIVENESS OF COGNITIVE-BEHAVIOURAL PSYCHOTHERAPY IN WILSON'S DISEASE: SINGLE SUBJECT EXPERIMENT - Roman, Ovidiu Teofil (Journal of Psychological and Educational Research, 2021)
Wilson's disease is a rare pathology, characterised by the uncontrolled accumulation of copper in the body predominantly affecting organs such as liver, brain, eyes. Multiorgan damage leads to a rapid deterioration of body functions, with major psychological and neurological impact. Therapeutic approaches are hampered by the low prevalence of the disease and by the impossibility of organising studies based on samples of subjects. For this reason, we set out to perform an experiment with a single patient diagnosed with Wilson's disease, in which we aim to highlight the effectiveness of psychotherapeutic interventions in mitigating the impact of the disease at the systemic level. Specifically, we want to analyse how the cognitive-behavioural therapy associated with relaxation techniques leads to the improvement of affective and motor symptoms, compared to thought suppressing techniques and techniques that involve the voluntary blocking of undesirable behaviour. The results indicate a significant improvement in behaviour and mood in the patient diagnosed with Wilson's disease following the use of cognitive restructuring techniques associated with muscle relaxation procedures.